Selection of Optimal Tests to Assess Transplantation Efficiency of Cryopreserved Progenitor Cells to Rats with Intracerebral Haemorrhage - Zolotko, Kirill N. (Problems of Cryobiology and Cryomedicine, 2017)
Probl Cryobiol Cryomed 2017; 27(2):168.